Hydrogen Sulfide Measurement of Degraded Corrosion Inhibitor with Glass Tube Detector in Oil & Gas Industry - Ni Made Truly Pinanti Sastra; Indri H. Susilowati (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Corrosion inhibitor (CI) is injected as carbon steel pipe corrosion protection with sulfur-containing substances in the product. One type of them is thioglycolic acid (TGA). Besides having benefits in maintaining pipe integrity, TGA can be decomposed to HS (hydrogen sulfide) due to changes in ambient temperature during storage, such as direct sunlight exposure on the field. This irritant gas can pose a risk to the health of chemical workers. Therefore, this study aims to measure the concentration of H2S in a CI product containing TGA. Method: The data were collected from an oil and gas company measurement report on 12 CI drums with 1-3%w of TGA content by using a glass tube detector. Measurements were performed by varying the measurement distance (0 and 10 cm from the mouth of the drum), observing the condition of the inflated drum surface, and determining the existence of internal pressure. Results: All samples were contained H2S, and the inflated drums had higher H2S content than those that were not inflated up to more than 200 ppm in the drum bore. At this concentration, workers can experience pulmonary edema significantly prolonged exposure. Biological monitoring can be done by analyzing thiosulfate content in urine and blood after exposure or routine examination at the end of the work shift. Conclusion: CI with TGA content has the potential of high H2S concentration, and it requires risk control such as engineering control, administration control, and PPE application to minimize the health impact of H2S exposure to the workers.